Effects of acupuncture in patients with chronic kidney disease: a systematic review - Geórgia Alcântara Alencar Melo; Letícia Lima Aguiar; Renan Alves Silva; Francisco Gilberto Fernandes Pereira; Fabiana Larissa Barbosa da Silva; Joselany Áfio Caetano
ABSTRACT Objectives: to analyze the effects of acupuncture techniques in patients with chronic kidney disease. Methods: a systematic review conducted in six databases, from September to December 2017, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses' criteria. The following descriptors were used: Acupuncture AND Chronic Renal Insufficiency AND Clinical Trial. Results: nine studies were selected; the acupuncture techniques used were auriculotherapy, electroacupuncture and acupressure aimed at improving quality of life, fatigue, sleep and clinical variables of the disease. The studies that assessed quality of life, sleep and fatigue presented significant benefits. Studies that assessed quality of life, sleep and fatigue presented significant benefits. There was no statistical significance in the improvement of serum creatinine levels and glomerular filtration rate. Methodological and assessment tools' divergence made impossible meta-analysis Conclusions: studies reinforce the positive effect of acupuncture in improving quality of life, fatigue and sleep in patients.